Evaluation of the posttraumatic growth inventory after severe burn injury in Western Australia: clinical implications for use - Martin, L.; Byrnes, M.; McGarry, Sarah; Rea, S.; Wood, F. (Informa Healthcare, 2016)
© 2015 Taylor & Francis. Purpose: Posttraumatic growth (PTG) is “the subjective experience of positive psychological change reported as a result of the struggle with trauma”. Very few studies have explored PTG after burn injury. The Posttraumatic Growth Inventory (PTGI) is a 21-item questionnaire which assesses five domains in which PTG has been found. First, the aim of this study was to assess how PTG presented after a severe burn, and second, whether it could be measured by the PTGI in Australian burn survivors. Methods: A mixed method approach was used. Seventeen patients who had a severe burn injury at least 2 years previously were interviewed and completed the PTGI. The interviews were analyzed, then compared to the PTGI responses. Results: PTG in burn survivors had similarities to PTG arising from other trauma. Burn-specific context such as heat intolerance and functional problems influenced the type of changes made. Barriers to PTG in relationships were related to guilt burden and visible scarring. Conclusion: PTG presents similarly after burn to other trauma types, but has other features to consider when devising intervention strategies. The PTGI is a 5-min screening tool that adequately identifies the presence or absence of PTG in burn survivors in Western Australia, and can guide intervention. Implications for rehabilitation: The Posttraumatic Growth Inventory is a 5-min screening tool that adequately identifies the degree of PTG in burn survivors in Western Australia. It is a quick and easy tool to use to identify the need for clinical intervention. It will also evaluate the effectiveness of strategies designed to target PTG. A mean score of 2.5 can be used as a threshold to guide intervention strategy.